“I Am a Princess Who Moves Around a Lot”: Syrian Refugee Women and the Shifting Roles and Responsibilities During Early Settlement in Southwestern Ontario - Telfah, Rana (Refuge, 2025)
This article takes a feminist approach to understanding Syrian refugee women’s early settlement experiences in small southwestern Ontario communities. It draws on interviews with Syrian refugee women who arrived in Canada with their families, sometimes without husbands, in 2016–2019. It is argued that the refugee journey and resulting shifts in Syrian women’s reproductive activities, including when they settle in rural/small-town southwestern Ontario, help them find a voice, giving them greater independence and power within their families. This study emphasizes the gendered nature of household production and contributes to literature on social reproduction by exploring the often-overlooked context of refugee resettlement. Findings highlight the necessity for policies that provide better support for refugee women during early settlement.